Comparison of DNA Damage and Oxidative Stress in Patients Anesthetized With Desflurane Associated or Not With Nitrous Oxide: A Prospective Randomized Clinical Trial - Nogueira, Flávia R [UNESP]; Braz, Leandro Gobbo [UNESP]; Souza, Kátina M [UNESP]; Aun, Aline G [UNESP]; Arruda, Nayara M [UNESP]; Carvalho, Lídia R [UNESP]; Chen, Chung-Yen O; Braz, José Reinaldo C [UNESP]; Braz, Mariana Gobbo [UNESP] (Wolters Kluwer, 2018)
BACKGROUND: Little is known about the effects of desflurane associated or not with nitrous oxide (N2O) on oxidative stress and patient genetic material. The aim of this study was to compare the effects of anesthesia maintained with desflurane associated or not with N2O on DNA damage (as a primary outcome) and oxidative stress (as a secondary outcome) in patients who underwent an elective minimally invasive surgery. METHODS: This prospective randomized clinical trial analyzed 40 patients of both sexes with an American Society of Anesthesiologists physical status I who were 18–50 years of age and scheduled for septoplasty. The patients were randomly allocated into 2 groups according to anesthesia maintenance as follows: desflurane (n = 20) or desflurane/N2O (n = 20). Blood samples were collected before anesthesia (T1 = baseline), 1.5 hours after anesthesia induction (T2), and on the morning of the postoperative first day (T3). Basal and oxidative DNA damage (determined using formamidopyrimidine DNA glycosylase to detect oxidized purines and endonuclease III to detect oxidized pyrimidines) were evaluated using the comet assay. Oxidative stress markers were evaluated based on lipid peroxidation (by assessing 4-hydroxynonenal and 8-iso-prostaglandin F2α [8-isoprostane] using enzyme linked immunosorbent immunoassay), protein carbonyls (assessed by enzyme linked immunosorbent immunoassay), and antioxidant defense (ferric-reducing antioxidant power by spectrophotometry). The effect size was expressed as the mean differences between groups and the corresponding 95% confidence interval (CI). RESULTS: There was no significant mean difference between groups in relation to DNA damage (−1.7 [95% CI, −7.0 to 3.5]), oxidized DNA pyrimidines (−1.8 [95% CI, −12.5 to 8.9]) and purines (−1.9 [95% CI, −13.9 to 10.1]), 4-hydroxynonenal (−0.2 [95% CI, −2.8 to 2.4]), 8-iso-prostane (549 [95% CI, −2378 to 3476]), protein carbonyls (0.2 [95% CI, −2.1 to 2.3]), or ferric-reducing antioxidant power (24 [95% CI, −52.0 to 117.2]). CONCLUSIONS: The coadministration of 60% N2O with desflurane did not seem to impair the effects on DNA or the redox status compared with desflurane anesthesia, suggesting that both studied anesthetic techniques can be suitable options for healthy individuals who undergo minimally invasive surgery lasting at least 1.5 hours. However, due to the low power of the study, more research is necessary to confirm our findings.